2009
DOI: 10.1080/01635580802398430
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Selenium on Benign and Malignant Prostate Epithelial Cells: Stimulation of LNCaP Cell Growth by Noncytotoxic, Low Selenite Concentrations

Abstract: We examined the hypothesis that nontoxic concentrations of selenium induce apoptosis and growth inhibition selectively in prostate cancer cells but not in benign prostate cells. Nontumorigenic BPH-1 prostate epithelial cells, androgen-sensitive LNCaP, and androgen-independent PC-3 prostate cancer cells were exposed to sodium selenite at 1 to 10 μmol/l for 24 to 72 h. Cell proliferation, viability, and apoptosis were assessed by MTT assay, trypan blue exclusion, flow cytometry, DNA laddering, and caspase activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 48 publications
(45 reference statements)
1
21
0
Order By: Relevance
“…In one of these studies, α-tocopherol increased the incidence of prostate cancer, similar to the results of SELECT [60]. We found that selenium at physiological concentrations increased cell proliferation in LNCaP prostate cancer cells in vitro, but inhibited proliferation at higher doses [62]. These findings can be interpreted as consistent with a postulated U-shaped dose response for selenium and cancer preventive effects [63].…”
Section: Chemopreventionsupporting
confidence: 78%
“…In one of these studies, α-tocopherol increased the incidence of prostate cancer, similar to the results of SELECT [60]. We found that selenium at physiological concentrations increased cell proliferation in LNCaP prostate cancer cells in vitro, but inhibited proliferation at higher doses [62]. These findings can be interpreted as consistent with a postulated U-shaped dose response for selenium and cancer preventive effects [63].…”
Section: Chemopreventionsupporting
confidence: 78%
“…Among these, selenium metabolites have been postulated to selectively promote apoptosis and inhibit proliferation of cancer cells. It has also been proposed that selenium supplementation of individuals with low selenium status may increase the expression of antioxidant selenoproteins and thereby prevents DNA damage that could lead to mutations and subsequent carcinogenesis [68]. …”
Section: Introductionmentioning
confidence: 99%
“…Besides SeR, both lycopene (LY), a dietary carotenoid synthesized by plants, fruits, and microorganisms with a strong antioxidant activity, and selenium (Se), an essential trace element mainly functioning through seleno-proteins and able to promote an optimal antioxidant/oxidant balance, have been shown to exert beneficial effects in BPH (12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%